“HAYATIN YILDIZ” YÖNTEM : Üç Saniyelerde Stres Azaltmak ve diğer insanlara fayda sağlayan insanlar olmak için Üç Anında Adımlar. - Indra Gunawan, Cakti (International Research & Development for Human Beings (IRDH), 2024)
star of life method: “Reducing Stress in Three Seconds and for all people Three Instant steps to be helpful.” Titled book. This book is suitable for use at home, in the office, at university and It is expected to help every individual who is stressed due to life pressure in other environments. This book is for adolescents, adults and adults without knowing the differences of religion, tribe, class and social status. It can be read by parents as well. This book, which is in Turkish, is especially for Turkish speakers. The author believes that this Turkish book will help people who use Turkish in the world to understand the content of this book more quickly. Hope it will make it easier for you to use it.